2004
DOI: 10.1002/jclp.20014
|View full text |Cite
|
Sign up to set email alerts
|

Individual and cultural‐diversity competency: Focus on the therapist

Abstract: The Competencies Conference: Future Directions in Education and Credentialing in Professional Psychology was held in Arizona in November 2002. One of the workshops, Individual and Cultural Differences (ICD), focused on racism, homophobia, and ageism. The consensus was that self-awareness and knowledge about the three "isms" are critical components in the education and training of psychologists. This article, authored by four of the workshop attendees, is a review of the current research and theoretical literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 56 publications
3
35
0
5
Order By: Relevance
“…APA's Ethics Code (American Psychological Association, 2002b) underscores the importance of competence in the domain of individual and cultural diversity, which includes attention to age, gender, gender identity, race, ethnicity, culture, national origin, religion, spirituality, sexual orientation, disability, language, and socioeconomic status. We concur with the delegates at the Competencies Conference who emphasized the value of psychologists' self-awareness and knowledge with regard to racism, homophobia, and ageism in all aspects of psychological practice (Daniel, Roysircar, Abeles, & Boyd, 2004) and believe these must be a focus of training for family psychology trainees. Despite the burgeoning interest in contextually sensitive family interventions and culturally competent family research, it is unfortunate that contextually sensitive supervision models are less well developed within family psychology (Todd & Storm, 2002).…”
Section: Individual and Cultural Diversitysupporting
confidence: 62%
“…APA's Ethics Code (American Psychological Association, 2002b) underscores the importance of competence in the domain of individual and cultural diversity, which includes attention to age, gender, gender identity, race, ethnicity, culture, national origin, religion, spirituality, sexual orientation, disability, language, and socioeconomic status. We concur with the delegates at the Competencies Conference who emphasized the value of psychologists' self-awareness and knowledge with regard to racism, homophobia, and ageism in all aspects of psychological practice (Daniel, Roysircar, Abeles, & Boyd, 2004) and believe these must be a focus of training for family psychology trainees. Despite the burgeoning interest in contextually sensitive family interventions and culturally competent family research, it is unfortunate that contextually sensitive supervision models are less well developed within family psychology (Todd & Storm, 2002).…”
Section: Individual and Cultural Diversitysupporting
confidence: 62%
“…The APA's Ethics Code (American Psychological Association, 2002b) underscores the importance of competence in the domain of individual and cultural diversity, which includes attention to age, gender, gender identity, race, ethnicity, culture, national origin, religion, spirituality, sexual orientation, disability, language, and socioeconomic status. We concur with the delegates at the Competencies Conference who emphasized the value of psychologists' self‐awareness and knowledge with regard to racism, homophobia, and ageism in all aspects of psychological practice (Daniel, Roysircar, Abeles, & Boyd, 2004) and believe that these must be a focus of training for family psychology trainees. Despite the burgeoning interest in contextually sensitive family interventions and culturally competent family research, it is unfortunate that contextually sensitive supervision models are less well developed within family psychology (Todd & Storm, 2002).…”
Section: Individual and Cultural Diversitysupporting
confidence: 63%
“…17 Further, researchers have found that when the community does look for care, there is a high likelihood that ethnic/racial communities, including American Indians, will receive health services from mainstream Caucasian therapists. 18 This is evidence of the dire need for cultural competence education for health care professionals.…”
Section: Needsmentioning
confidence: 99%